Gut Microbiota Interventions With Clostridium butyricum and Norfloxacin Modulate Immune Response in Experimental Autoimmune Encephalomyelitis Mice - Chen, Hao; Ma, Xiaomeng; Liu, Yingying; Ma, Lili; Chen, Zhaoyu; Lin, Xiuli; Si, Lei; Ma, Xueying; Chen, Xiaohong (Frontiers in Immunology, 2019)
Gut microbiota has been proposed as an important environmental factor which can intervene and modulate CNS autoimmunity. Here, we altered the composition of gut flora with C. butyricum and norfloxacin in experimental autoimmune encephalomyelitis (EAE), an animal model of Multiple sclerosis. We found that appropriate C. butyricum (5.0×106 CFU/mL intragastrically/daily, staring at weaning period of age) and norfloxacin (5 mg/kg intragastrically/daily, one week prior to EAE induction) treatment could both ameliorate EAE although there are obvious differences in gut microbiota composition between these two interventions. C. butyricum increased while norfloxacin decreased the abundance and diversity of the gut microbiota in EAE mice, and both of the treatments decreased firmicutes/bacteroidetes ratio. In the genus level, C. butyricum treatment increased the abundance of Prevotella while Akkermansia and Allobaculum increased in norfloxacin treatment. Moreover, both interventions reduced Desulfovibroneceae and Ruminococcus species. Although the discrepancy in the gut microbiota composition with the two interventions, C. butyricum and norfloxacin treatment both reduced Th17 response and increased Treg response in the gastrointestinal tract and extra-gastrointestinal organ systems in EAE mice. And the reduced activity of p38 MARK and JNK signaling in spinal cord could be observed in the two interventions. The results suggested that manipulation of gut microbiota interventions should consider many factors such as timing, duration and dosage. The discrepancy in the composition and the similar protective T cells response of C. butyricum and norfloxacin imply that achieving intestinal microecology balance by promoting and/or stimulating the gut microbiota contribute to the well-being of immune response in EAE mice.